2019
DOI: 10.3389/fnbeh.2019.00233
|View full text |Cite
|
Sign up to set email alerts
|

Social Memory and the Role of the Hippocampal CA2 Region

Abstract: The CA2 region of the hippocampus is a somewhat obscure area lacking in an understanding of its form and function. Until recently, the CA2 has been thought of as merely an extension of the CA3, with some referring to it as the CA3a region. Recent investigations into this area have not only delineated the CA2, but also defined it as a region distinct from both CA1 and CA3, with a unique set of cortical inputs and outputs and contributions to cognitive processes. One such process that has been shown to depend on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 101 publications
5
54
0
Order By: Relevance
“…Using an optogenetic approach, Raam et al ( 2017 ) identified in the hippocampus an output from anterior CA2/CA3 regions to posterior CA1 as the pathway of social stimuli discrimination. These results are consistent with the recognized role of the hippocampus on social cognition regulation (Alexander et al, 2016 ; Okuyama et al, 2016 ; Danjo et al, 2018 ; Phillips et al, 2019 ; Tzakis and Holahan, 2019 ). This regulation is highly associated with the hippocampal posterior CA1 region projection to the prefrontal cortex, hypothalamus, and amygdala, key parts of the emotional reactivity and SDN (Hitti and Siegelbaum, 2014 ; Okuyama et al, 2016 ; Smith et al, 2016 ).…”
Section: Discussionsupporting
confidence: 89%
“…Using an optogenetic approach, Raam et al ( 2017 ) identified in the hippocampus an output from anterior CA2/CA3 regions to posterior CA1 as the pathway of social stimuli discrimination. These results are consistent with the recognized role of the hippocampus on social cognition regulation (Alexander et al, 2016 ; Okuyama et al, 2016 ; Danjo et al, 2018 ; Phillips et al, 2019 ; Tzakis and Holahan, 2019 ). This regulation is highly associated with the hippocampal posterior CA1 region projection to the prefrontal cortex, hypothalamus, and amygdala, key parts of the emotional reactivity and SDN (Hitti and Siegelbaum, 2014 ; Okuyama et al, 2016 ; Smith et al, 2016 ).…”
Section: Discussionsupporting
confidence: 89%
“…Using MRI analysis, we found no major structural alterations in the brain of our mutants except larger olfactory bulbs and a smaller hippocampus. Our data are in agreement with studies showing that the hippocampus plays a critical role in social memory and recognition (Kogan et al, 2000;Maaswinkel et al, 1996;Okuyama, 2018;Raam et al, 2017;Tzakis and Holahan, 2019). It is possible that social memories also rely on different subregions of the hippocampus, different networks and connections and/or different molecular pathways.…”
Section: A Central Role Of the Hippocampus In Scrib Dependent Social supporting
confidence: 92%
“…Overall, delayed maturation of PNNs in the CA1 might be responsible for long-lasting cognitive/psychiatric impairments. The hippocampal area CA2 is required for the formation of social memories, and particularly social recognition memory, namely the ability to recognize a novel or familiar conspecific [ 118 ]. The CA2 contains a population of large pyramidal neurons [ 119 ], which are surrounded by prominent PNNs.…”
Section: Pnns and Brain Maturationmentioning
confidence: 99%